Bias of Damage Awards and Free Options in Securities Litigation - Dybvig, Philip H.; Gong, Ning; Schwartz, Rachel (Journal of Financial Intermediation, 2000)
Damage measures in securities fraud cases are very imprecise because they are based on security price changes that reflect both the correction of previous misrepresentation and other independent information. Consequently, potential plaintiffs have a valuable “free option” to decide whether or not to file suit, and average damage awards are greater than actual damages, much greater when markets are volatile. The “Private Securities Litigation Reform Act of 1995” was intended to curb abusive litigation and to address the problem of excessive damage awards. Motivated by a misdiagnosis that excess awards are due to temporary price drops, the Act limits damages to the difference between the purchase price and the time-averaged trading price from the release of the corrective information until 90 days later or until the sale of the security, whichever is first. Unfortunately, the Act's modified measure of damages suffers from a more severe free-option problem than did the traditional measure. Also, the Act introduced an additional new option to time the sale of the security; the effects of these options may be mitigated by the impact of the positive drift in stock prices over time, if the time-averaged price is not adjusted for market movements. As a result, the bias can be larger or smaller under the new Act, depending on how severe the free-option problem is. We propose an alternative approach to addressing the issue of excessive damages: courts should adopt a threshold of measured damages below which no damage would be awarded. The threshold would depend on several factors, most notably the volatility of the stock in the period under question. That is, damages will be awarded only if measured damages exceed the threshold, and awards would be capped by the formula presented in the Reform Act. Journal of Economic Literature Classification Numbers: K22, G38.